A study on the utility of the media magazine for communicating sustainable regional development in Sri Lanka (with special reference to Peramaga magazine) - K. P., Gamage (My University, 2021)
Magazines describe branded and edited contents often supported by advertising or sponsorshipand delivered in print or other forms. It is noted that magazines are printed periodicallyandcommonly published weekly, monthly or quarterly. Western communication historydefinespublications appearing at regular intervals (weekly, monthly, and quarterly) other thannewspapers, generally or smaller size with cover and binding periodicals and journals togeneral circulation as magazines. The Brundtland Commission report defines sustainable development as "development which meets the needs of current generations without compromising the abilityof future generations to meet their own needs". This concept strongly supports economicandsocial development in particular, of regional people. At the same time, it underlines theimportance of protecting the natural resource base and the environment. The magazineof'Peramaga' was first published in March, 1979by the Ministry of Provincial Council and Local Government Bodies. The aim of this magazine is to communicate projects that were launchedby the Ministry and to ensure accuracy, knowledge and better vision for government officers and the community. This study focuses on the utility of magazine media for communicatingsustainable regional development and applies a mixed methodology with qualitativeandquantitative data. Interviews, content analysis and observation of selected magazines areemployed as tools for collecting data. “Peramaga” magazine basically bears the ideologyof theMinistry and communicates projects of “Uda Gam”, "Pooja bhoomi sanvardhane", "Gamudha"carried out by the Ministry in order to develop sustainable regional development.
Keywords: Magazine; Sustainable Development; Social Development; Communication; Regional People